A Range of Writing Across the Content Areas. (23rd September 2013) - Fisher, Douglas; Frey, Nancy
Abstract Students must be taught to write and then be expected to write for a variety of purposes to a variety of audiences, including in mathematics, science, and social studies. As part of building the writing prowess of students, they must write routinely, both short and long pieces. As part of a comprehensive writing curriculum, students' writing fluency should be fostered, students should participate in lessons designed to build their composing skills, and students must learn to write from the sources that they read.